Total Knee Replacement Epidemiology Before and After the COVID-19 Pandemic: A Descriptive Comparative Study - Endrotomo Sumargono; Maria Anastasia; Ifran Saleh; Astuti Pitarini; Maria Florencia Deslivia; Claudia Santosa; Erica Kholinne (The Hip and Knee Journal, 2021)
Background: The purposes of this study were (1) to describe the characteristics of patients underwent TKR during COVID-19 Pandemic and (2) to compare the demographic of patients underwent TKR before and after COVID-19 Pandemic in St. Carolus Hospital, Jakarta, Indonesia.Methods: Data were extracted from January 2016 to December 2020 from the annual reports of arthroplasty registry (single surgeon). Patient demographic data were collected (Gender, age, comorbidity). Post-operative characteristics were defined as: (1) Length of hospitalization (days); (2) Complication rate (%); (3) Revision event (%). The complication rate included: (1) Deep vein thrombosis; (2) Prosthetic joint infection; (3) Periprosthetic fracture. The above parameters were compared before and after the COVID-19 Pandemic.Result: A total of 730 primary TKR procedures (12.3 cases per month) were performed from January 2016 to February 2020, meanwhile there were 54 primary TKR (6 cases per month) done in 9 months after COVID-19 Pandemic from March 2020 to December 2020. The lowest case monthly after the COVID-19 Pandemic was found on April 2020 (1 case per month), on the other hand, the highest case monthly was found on December 2020 (14 cases per month). The complication rate decreased from the Pre COVID-19 Pandemic (8.6% to 1.8%).Conclusion: The number of cases was reduced during Indonesia large-scale social restriction (40 %) and returned to the Pre-Pandemic period on December 2020.Level of Evidence : Descriptive study, level III